Sustainable Manufacturing – Architecture for Manufacturing System - Hussain, S.; Jahanzaib, M. (The Nucleus, 2018)
While research in Sustainable Manufacturing has tremendously been extended along numerous dimensions; it has sparked new needs and requirements for industrial and research community. This research has proposed and elaborated the architecture for Manufacturing System of a firm in relation to sustainability in manufacturing. Architecture is proposed as a set of five interdependent elements: ‘Context’, ‘Purpose’, ‘Function’, ‘Structure’, and ‘Process’. These elements have been conceptualized, in a wider context, from the perspective of larger containing systems (Enterprise, economic system, social system, and ecosystem). On this concept, essential content under each element has been framed keeping in view the salient requirements pertinent to Sustainable Manufacturing and the enterprise. Sustainability aspects relevant to a manufacturing firm are discussed alongside, in particular, from the perspective of emerging paradigm of Circular Economy. Architecture proposition is guided by research in Systems Thinking, Sustainable Manufacturing, and Manufacturing System. The research would serve as a guideline for manufacturing businesses towards systemic development and operation of a manufacturing system in view of environmentally conscious and economically sound manufacturing.